A physical map of traits of agronomic importance based on potato and tomato genome sequences - Gebhardt, Christiane (Frontiers in Genetics, 2023)
Potato, tomato, pepper and eggplant are worldwide important crop and vegetable species of the Solanaceae family. Molecular linkage maps of these plants have been constructed and used to map qualitative and quantitative traits of agronomic importance. This research has been undertaken with the vision to identify the molecular basis of agronomic characters on the one hand, and on the other hand, to assist the selection of improved varieties in breeding programs by providing DNA-based markers that are diagnostic for specific agronomic characters. Since 2011, whole genome sequences of tomato and potato became available in public databases. They were used to combine the results of several hundred mapping and map-based cloning studies of phenotypic characters between 1988 and 2022 in physical maps of the twelve tomato and potato chromosomes. The traits evaluated were qualitative and quantitative resistance to pathogenic oomycetes, fungi, bacteria, viruses, nematodes and insects. Furthermore, quantitative trait loci for yield and sugar content of tomato fruits and potato tubers, and for maturity or earliness were physically mapped. Cloned genes for pathogen resistance, few genes underlying quantitative trait loci for yield, sugar content and maturity and several hundred candidate genes for these traits were included in the physical maps. The comparison between the physical chromosome maps revealed in addition to known intrachromosomal inversions several additional inversions and translocations between the otherwise highly collinear tomato and potato genomes. The integration of the positional information from independent mapping studies revealed colocalization of qualitative and quantitative loci for resistance to different types of pathogens, called resistance hotspots, suggesting a similar molecular basis. Synteny between potato and tomato with respect to genomic positions of quantitative trait loci was frequently observed, indicating eventually similarity between the underlying genes.